2010
DOI: 10.1111/j.1473-4192.2009.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐scaffolding mediated by languaging: microgenetic analysis of high and low performers

Abstract: The growing literature about the positive effect of languaging or self‐explaining has so far failed to determine why some learners benefit from languaging more than others. We attempt to address this gap through a microgenetic analysis of the languaging behaviour of two university students learning French as a second language, whom we identify as a high and a low languager. We trace the development of their understanding of the grammatical concept of voice in French. Our findings suggest that languaging is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 18 publications
(35 reference statements)
3
38
0
Order By: Relevance
“…In this respect, there are similarities between the present study and studies on 'languaging' such as those by Swain and associates (e.g. Swain et al 2009;Knouzi et al 2010) which look at language learners' talking about language and the effect it might have on language learning outcomes. Languaging is admittedly a central feature of the group work data discussed below.…”
Section: Introductionmentioning
confidence: 39%
“…In this respect, there are similarities between the present study and studies on 'languaging' such as those by Swain and associates (e.g. Swain et al 2009;Knouzi et al 2010) which look at language learners' talking about language and the effect it might have on language learning outcomes. Languaging is admittedly a central feature of the group work data discussed below.…”
Section: Introductionmentioning
confidence: 39%
“…However, the findings reported to date provide promising evidence that warrants serious consideration of pedagogical alternatives to pervasive ones which rely primarily on discrete, often oversimplified, and even simplistic, pedagogical grammar rules. Examples of these studies include Van Compernolle (2012) who developed materials for the development of sociopragmatic knowledge of L2 French; Yáñez-Prieto (2008) who focused on verbal aspect in Spanish; Negueruela (2003Negueruela ( , 2008 for the development of verbal aspect, mood, and modality in Spanish; Author (2011) who looked at materials for the development of verbal aspect in English; and a series of publications by Swain, Lapkin and colleagues focusing on the concept of voice in French (Knouzi et al 2010, Lapkin et al 2008, Swain 2010Swain et al 2009). For comprehensive and in-depth overviews of studies based on CBI and Systemic-Theoretical Instruction refer to Lantolf andPoehner (2008, 2014).…”
Section: Enhancing Metalinguistic Knowledge Through Pedagogical Artifmentioning
confidence: 99%
“…This is an aspect that requires consideration and I will report in a subsequent paper, but further, large scale, empirical trials comparing various verbalization conditions are necessary (cf. Knouzi et al 2010, Lapkin et al 2008, Swain 2010, Author 2011 for studies on dyadic verbalization).…”
Section: Pedagogical Implications Limitations and Future Researchmentioning
confidence: 99%
“…In order to further determine why some learners benefited more from languaging than others, Knouzi et al (2010), through analyzing the languaging behaviors of a higher and a lower languager and tracing the development of their understanding of the French concept of voice in a microgenetic way, found that the higher languager not only produced more languaging but also engaged in better-quality languaging. Specifically, languaging served as a self-scaffolding tool for the higher languager, who could efficiently use it to solve cognitive conflicts, mediate mental processes, and construct meaning, while the lower languager tended to misinterpret the task and function of languaging, pursue different goals, and leave conflicts unresolved.…”
Section: A Studies On Oral Languaging In L2 Learningmentioning
confidence: 99%
“…Suzuki, 2012;Swain et al, 2009), the relation between languaging quantity and language learning (e.g. Knouzi et al, 2010), the relation between languaging quality and language learning (e.g. Suzuki, 2017), the mediating function of languaging (e.g.…”
Section: Critical Comments and Directions For Future Researchmentioning
confidence: 99%